The Complexities of the Field in a Linguistic Ethnographic Research - Blanka Barabás (Acta Universitatis Sapientiae: Philologica)
In critical sociolinguistics, language is viewed as a fundamentally social phenomenon that is defined discursively, rather than in terms of individual beliefs and attitudes, and because linguistic practices are themselves intersubjective. Moreover, the broader cultural, historical, and political aspects have also become relevant in the study of language, requiring new ways of addressing sociolinguistic issues. Linguistic ethnography may be a central tool in this inquiry, as it looks at everyday practices in order to understand wider social structures. In this paper, I argue that a festival as a place of encounters provides an adequate context for such research. After discussing the different concepts of the field in doing ethnographic work, I examine the online presence of the festival in question. Tusványos is an event organized in Transylvania every year, with the intention of bringing together Hungarian participants from Hungary and Romania, as well as Romanians.